Comparative analysis of the hedging effectiveness for soybean using ols and bivariate Garch Bekk Model - Caldarelli, Carlos Eduardo; Souza, Waldemar Antônio da Rocha de (Revista de Economia, 2011)
Dynamic hedging effectiveness for soybean farmers in Rondonópolis (MT) with futures contracts of BM&F-BOVESPA is calculated through optimal hedge determination, using the bivariate GARCH BEKK model, which considers the conditional correlations of the prices series, comparing the results with the minimum variance model effectiveness, calculated by OLS, the unhedged and the naïve hedge positions. The financial effectiveness of the dynamic hedge model is superior and can be used by farmers for several decision making purposes such as price discovery, hedging calibration, cash flow projections, market timing, among others.